Analisis Bentuk Lagu “Bhuana Santhi” Karya I Komang Darmayuda - I Pt. Lukita Wiweka Nugraha Putra; Komang Wahyu Dinata (Journal of Music Science, Technology, and Industry, 2023)
Purpose: This article is an analysis of the form of the song Bhuana Santhi by Komang Darmayuda. Bhuana Shanti performed by students of SMPN 1 Denpasar as Indonesia's representative in the 2014 international level vocal group (Celesta) has succeeded in making Indonesia proud as the best performer in the 2014 international vocal group event. The purpose of writing this article is to describe the form of the song Bhuana Shanti by Komang Darmayuda. Komang Darmayuda is the sole informant in writing this article. Method: This article focuses on the form of the song Bhuana Shanti by Komang Darmayuda in order to obtain the musical elements contained therein (melody, harmony/chord, and dynamics). Result and Discussion: Before obtaining the forms and musical elements contained in Bhuana Shanti's songs, the structure is first described, namely motifs, sentences, and periods. The musical elements that have been obtained through the process of analyzing structure and form will explain the beauty contained in the Bhuana Shanti song. Data in the form of numeric notation, audio, and information on the performance of the Bhuana Shanti song were obtained through direct observation and interviews with Komang Darmayuda as the composer of Bhuana Shanti. Analysis of the form of music is the most basic effort to find out the beauty contained in a piece of music. Implication: By writing this article, it is hoped that it can provide insight or material for consideration for future composers representing Indonesia in the international level vocal group (Celesta) event.